Penerapan Terapi Komplementer Relaksasi Otot Progresif Terhadap Penurunan Kadar Gula Darah Pasien Diabetes Melitus Tipe Ii Di Bangsal Sakura Rsud Dr.Soeratno Gemolong, Sragen - Putri Ana Devi; Ika Silvitasari; Fitria Purnamawati (STIKes Ibnu Sina Ajibarang, 2024)
Diabetes mellitus is a chronic disease characterized by high levels of glucose in the blood caused by insulin resistance. One way to help lower the patient's blood sugar levels is by practicing physical activity. Progressive muscle relaxation therapy can be an activity of choice for diabetes sufferers because it can reduce tension, reduce stress, and improve metabolic rate. Purpouse : to apply progressive muscle relaxation therapy, namely to determine the results of applying progressive muscle relaxation therapy to reduce blood sugar levels while in patients with type II diabetes mellitus. Methode : using a descriptive method in the form of a case study on two respondents by focusing on the implementation of progressive muscle relaxation therapy to reduce blood sugar levels in diabetes mellitus patients by providing intervention for three days. Results : progressive muscle relaxation therapy had an effect on reducing the patient's blood sugar levels so that the patient's blood sugar levels were reduced. The first patient's blood sugar level went from 251 mg/dl to 123 mg/dl and the second patient's blood sugar level went from 388 mg/dl to 141 mg/dl. Conclusion : Progressive muscle relaxation therapy in diabetes mellitus patients is effective in reducing the patient's blood sugar levels.